Professional zakat empowerment strategy for improving community welfare in Central Lombok - Junaidi, Junaidi; Malik, Abdul (Gema Wiralodra, 2024)
Professional zakat is one of the zakat instruments that can potentially improve the community's welfare. However, this potential has not been optimally exploited. Therefore, efforts are needed to improve the empowerment of zakat professionals. This study aims to analyze the strategy of empowering zakat professionals to improve community welfare in Central Lombok. This research uses qualitative research methods. This method collects data and information through in-depth interviews, observations, and document studies. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that professional zakat has great potential to improve community welfare. Empowering professional zakat to improve community welfare in Central Lombok can be done in several ways, including increasing public awareness, organized professional zakat management, adequate professional zakat policies and regulations. So it can be concluded that the potential for professional zakat in NTB Province is very large and can be an important source of funds to improve community welfare. Professional zakat empowerment strategies need to be prepared and implemented in a planned and structured manner so that they can have a significant impact on improving community welfare.